Pengaruh Persepsi Kualitas Produk, Citra Merek dan Media Iklan Instagram terhadap Keputusan Pembelian Produk Ninebox (Studi Kasus pada follower instagram @tempattasdotcom - Wiwik Widiyanti (Universitas Bina Sarana Informatika, 2017)
The phenomenon of the emergence of social media makes the businessman use it as a marketing gap, as well as Ninebox a famous multipurpose rack brand in Indonesia. Instagram as one of the advertising media chosen to support marketing. This research analyzes the relationship of perception of product quality, brand image and advertisement media instagram to purchase decision of ninebox product case study follower of @tempattasdotcom. The form of the research is quantitative descriptive with the type of survey research, and the correlational design of causality. Non-probability sampling method or non-random selection is purposive sampling. The results obtained that there is influence perception of product quality, brand image and media advertising instagram of the decision to purchase ninebox products